2015
DOI: 10.1002/2015gl064222
|View full text |Cite
|
Sign up to set email alerts
|

Hidden carbon sink beneath desert

Abstract: For decades, global carbon budget accounting has identified a “missing” or “residual” terrestrial sink; i.e., carbon dioxide (CO2) released by anthropogenic activities does not match changes observed in the atmosphere and ocean. We discovered a potentially large carbon sink in the most unlikely place on earth, irrigated saline/alkaline arid land. When cultivating and irrigating arid/saline lands in arid zones, salts are leached downward. Simultaneously, dissolved inorganic carbon is washed down into the huge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 34 publications
1
65
0
1
Order By: Relevance
“…Although soil CO2 uptake in deserts has been investigated in many previous studies, its potential influences on the groundwater environment remain unaddressed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. This is partially due to the lack of a simple method for the separation and quantification of such CO2 uptake.…”
Section: Implications Of Soil Co2 Uptake To the Groundwater Environmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Although soil CO2 uptake in deserts has been investigated in many previous studies, its potential influences on the groundwater environment remain unaddressed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. This is partially due to the lack of a simple method for the separation and quantification of such CO2 uptake.…”
Section: Implications Of Soil Co2 Uptake To the Groundwater Environmentmentioning
confidence: 86%
“…It has been widely recognized that the overall magnitude of CO2 dissolution beneath deserts and its contributions to the ecosystem carbon balance can be huge [30][31][32][33][34][35][36][37][38][39], but its effect on the local environment are seldom reported. As a first attempt to analyze the implications of the soil CO2 uptake to the groundwater environment, the present study simply assumes that the absorbed CO2 has been largely dissolved in the soil-groundwater system beneath the deserts.…”
Section: Implications Of Soil Co2 Uptake To the Groundwater Environmentmentioning
confidence: 99%
“…Because of the complexity of these processes involved in atmosphere-landscape relation, there are few reliable estimates of the pool of secondary carbonates in world desert soils [5,6,7,8,9,10], particularly in arid areas in northern China [11,12,13,14,15,16,17]. The global carbon balance includes a large terrestrial carbon sink, but that sink has not been fully identified nor its mechanisms explained [18,19,20,21,22,23]. Recent findings that desert regions remove carbon dioxide (CO2) from the atmosphere at a magnitude of ~100 g Cm -2 yr -1 suggest that these systems may explain at least a portion of that terrestrial carbon sink [23,24,25,26,27,28].…”
Section: +mentioning
confidence: 99%
“…The global carbon balance includes a large terrestrial carbon sink, but that sink has not been fully identified nor its mechanisms explained [18,19,20,21,22,23]. Recent findings that desert regions remove carbon dioxide (CO2) from the atmosphere at a magnitude of ~100 g Cm -2 yr -1 suggest that these systems may explain at least a portion of that terrestrial carbon sink [23,24,25,26,27,28]. Stone (2008) [25] suggests that a significant loop in the carbon cycle may be hidden in the global desert areas (both low latitude and middle latitude), because two of the northern middle-latitude deserts, the Gulbantonggut Desert of northwestern China [27] and the Mojave Desert of western USA [26], were both observed to be soaking up the surrounding CO 2 in an inorganic-salt form at a surprising rate.…”
Section: +mentioning
confidence: 99%
“…Such inorganic processes may introduce fluctuations not only to hourly or diurnal soil CO 2 effluxes (e.g. Emmerich, 2003;Xie et al, 2009;Buysse et al, 2013) but also to terrestrial CO 2 sinks at much broader spatiotemporal scales (Schlesinger, 2009;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%